Code-Mixing and literal translation in Nepal’s English newspapers - Poudel, Sagar (Journal of NELTA, 2019)
This study examines the texts published in English newspapers in Nepal to find out the code mixing and literal translation of Nepali language. For the study, the data were taken from the secondary sources. Mainly two English newspapers, The Himalayan Times and The Kathmandu Post published in Nepal were taken as the sources of the data purposively. Code mixing is the use of code from one language into another language in the course of using it in communication. Similarly, literal translation is translating the source language text into the target language text with the equivalence of structure, lexicon and morphology. Such code mixing and literal translation brings variation into target language. The study found out that the codes, which are associated with religion, particular culture, local context and situations are mixed with English language. Similarly, the popular expressions among the Nepalese context were found literally translated.